2017
DOI: 10.1111/imr.12567
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota: Role in pathogen colonization, immune responses, and inflammatory disease

Abstract: Summary The intestinal tract of mammals is colonized by a large number of microorganisms including trillions of bacteria that are referred to collectively as the gut microbiota. These indigenous microorganisms have co-evolved with the host in a symbiotic relationship. In addition to metabolic benefits, symbiotic bacteria provide the host with several functions that promote immune homeostasis, immune responses and protection against pathogen colonization. The ability of symbiotic bacteria to inhibit pathogen co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
929
1
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,243 publications
(949 citation statements)
references
References 238 publications
(425 reference statements)
3
929
1
16
Order By: Relevance
“…In particular, Enterobacteriaceae populations expand during bouts of inflammation (Lupp et al, 2007;Garrett et al, 2010). The outgrowth of these pathobionts in turn exacerbates intestinal inflammation, epithelial cell damage, and wound repair responses (Carvalho et al, 2012;Gronbach et al, 2014;Kang and Martin, 2017;Pickard et al, 2017), thus amplifying known risk factors of CAC development.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Enterobacteriaceae populations expand during bouts of inflammation (Lupp et al, 2007;Garrett et al, 2010). The outgrowth of these pathobionts in turn exacerbates intestinal inflammation, epithelial cell damage, and wound repair responses (Carvalho et al, 2012;Gronbach et al, 2014;Kang and Martin, 2017;Pickard et al, 2017), thus amplifying known risk factors of CAC development.…”
Section: Introductionmentioning
confidence: 99%
“…In Nicaragua, Lactobacillus, Lachnospiraceae, Bifidobacterium, Ruminococcaceae and Veillonella were identified as responsive following rice bran consumption compared to an age and control matched group. These taxa have recognized saccharolytic mechanisms of action 6567 , are known to produce and promote crossfeeding of short chain fatty acids 68, 69 , as well as provide competitive inhibition of pathogen colonization 70, 71 . The microbial enrichment of these communities as associated with infant growth outcomes has implications for assessing how gut microbes metabolize rice bran components.…”
Section: Discussionmentioning
confidence: 99%
“…127,128 For example, the glycosylation of intestinal epithelial cells can be regulated by dendritic cells and innate lymphoid cells (ILC3s). With regard to iNKT cells, it was suggested that iNKT cell-derived interleukin-13 (IL-13) regulates goblet cell homeostasis.…”
Section: (3) Mucus Production and Glycosylationmentioning
confidence: 99%